1996
DOI: 10.1192/bjp.168.6.745
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Study of Dementia in a Rural Community in Kerala, India

Abstract: Dementia is an important cause of morbidity in the geriatric population in this community, where families take responsibility for the care of relatives with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
133
7
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(156 citation statements)
references
References 6 publications
13
133
7
3
Order By: Relevance
“…Sete estudos populacionais sobre o assunto, realizados recentemente em países em desenvolvimento, 2,14,19,21,23,26,32 com metodologias adequadas para seus contextos culturais, apresentaram resultados consistentes de prevalências de demência ajustadas por idade inferiores às encontradas nos estudos realizados na Europa, 6 tanto para pessoas com 60 anos ou mais (variação entre os estudos: 1,3% a 5,3%), como para pessoas com 65 anos ou mais (variação entre os estudos: 1,7% a 5,2%). Três destes estudos foram realizados na Índia, 2,23,26 dois na China, 19,32 um na Tailândia 21 e um na Nigéria.…”
Section: Epidemiologia Da Demência Em Países Em Desenvolvimentounclassified
“…Sete estudos populacionais sobre o assunto, realizados recentemente em países em desenvolvimento, 2,14,19,21,23,26,32 com metodologias adequadas para seus contextos culturais, apresentaram resultados consistentes de prevalências de demência ajustadas por idade inferiores às encontradas nos estudos realizados na Europa, 6 tanto para pessoas com 60 anos ou mais (variação entre os estudos: 1,3% a 5,3%), como para pessoas com 65 anos ou mais (variação entre os estudos: 1,7% a 5,2%). Três destes estudos foram realizados na Índia, 2,23,26 dois na China, 19,32 um na Tailândia 21 e um na Nigéria.…”
Section: Epidemiologia Da Demência Em Países Em Desenvolvimentounclassified
“…12 A study in a rural community in Kerala showed a prevalence of 33.9 per 1000 in people aged 60 years and above. 13 Compared to this study, a western study showed a higher prevalence rate (9.8%). 14 Prevalence of dementia varied from one study to another depending on the geographical area and the demographic profile of the study population.…”
Section: Discussionmentioning
confidence: 74%
“…The prevalence of dementia in rural population of South India and North India showed a widely varying rate ranging from 3.39 to 0.84%, respectively. 4,5 In two other studies conducted in Jammu district, the prevalence was found to be 1.83% in Chattha zone while it was 6.55% in Mishriwala area of Jammu. 6,7 A higher prevalence in our study could be attributed to different lifestyles of local population versus Kashmiri migrant population, lesser awareness and illiteracy among people residing in these zones.…”
Section: Discussionmentioning
confidence: 99%